Separating The Wheat From The Chaff: Delimiting Public Policy Influence On The Arbitrability Of Disputes In Africa - Ogunranti, Akinwumi (Journal of Sustainable Development Law and Policy, 2025)
This article focuses on the arbitrability of disputes. It examines the recent global trend of delimiting the role of public policy in determining matters that should be subject to arbitration. The evaluation shows that the application of doctrines of separability and kompetenz-kompentenz plays a vital role in the delimitation process. However, notwithstanding the global trend to restrict the role of public policy in determining arbitrability, some countries in Africa still widely interpret public policy to revoke arbitral clause, stay arbitral proceedings, or refuse enforcement of foreign arbitral awards. They justify this approach on the basis that public policy is a means to protect national economic interest against foreign manipulation or exploitation. Anchored on Morgan’s theoretical approach, this article criticizes the excessive role of public policy in determining the arbitrability of disputes in Africa. It calls for a change to reflect the global trend through judicial activism and legislative reform. Although protecting national economic interest is an important goal, restricting matters that are arbitrable will not promote foreign investment. Therefore, countries in Africa must fashion arbitration practices that reflect their socio-economic background as well as contemporary arbitral trends around the world.